6n -3=2n+9 6n-2n=9+3 4n=12 n=12/4 n=3
The nth term IS 4n + 3 ie 4 times n and then add 3.
The answer is n = 5.
10x + 3 = 15 10x = 15 - 3 10x = 12 x = 1.2
5 + -8 = 3 + 12 -3 is not equal to 15
1
4n + 3 = 31n 3 = 27n n = 3/27
3 + 3n = 9 + 2n + 4n n = -2
N=3.
4n+13=1 -13 -134n=-12/4 /4n=-3
n= -2
To solve for n in the equation 4n + 3 = 19, you first need to isolate the variable n. Start by subtracting 3 from both sides of the equation to get 4n = 16. Then, divide both sides by 4 to find n = 4. Therefore, the solution to the equation is n = 4.
4n + 9 = -3 Now, we take away 9 from both sides 4n = -12 Now divide by 4 n = -3
3n+18 = 39 -4n 3n+4n = 39 -18 7n = 21 n = 3
6n - 4 - 3 = 3n + 10 + 4n -7 = 7n - 6n + 10 -17 = n
7n + 2 = 4n + 17Subtract 2 from each side:7n = 4n + 15Subtract 4n from each side:3n = 15Divide each side by 3:n = 5
Subtracting 3n from each side gives 12 = 4n or 4n = 12. n = 12/4 n = 3